Modification of optical properties and structure of thin films for enhancing absorption - Lysiuk, V.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
The most used methods such as ion implantation, laser irradiation and
nanosphere lithography for modification and creation of special microrelief of thin
absorbing films on photosensitive substrates have been described. Controlled
modification of surface structure of the samples for improving their optical properties,
especially for enhancing absorption, has many applications in optical devices. The basic
things were analyzed from selection of film materials and ways for their further
processing to shapes and dimensions of the obtained surface structures. Theoretical
modeling methods based on the Mie theory and statistical temporal mode-coupled theory
have been used to explain the influence of surface microrelief on optical properties of the
samples. Advantages and perspectives for application of the methods have been
described and analyzed.